2013
DOI: 10.4274/turkderm.90277
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive vellus hair cysts on the face: a case report and literature review

Abstract: ÖzetEruptif vellus kıl kisti genelde göğüs ve ekstremitelerde ortaya çıkan, çok sayıda, asemptomatik, komedon benzeri papüllerle karakterize, ender rastlanan bir deri hastalığıdır. Çocuk ve genç erişkinlerde daha sık görülmektedir. Etyolojisi tam bilinmeyen rahatsızlık sporadik şekilde gelişebileceği gibi otozomal dominant yolla kalıtsal geçiş de gösterebilmektedir. Burada; yüzün alın ve yanak bölgelerinde yoğun yerleşim gösteren, çok sayıda, grimsi sarı-renginde papülleri bulunan, eruptif vellus kıl kisti tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Because those in the facial area mostly do not regress spontaneously and pose cosmetic problems for the patient, they are treated surgically by total excision. 11 In our study, VHC was identified only in 1 case, in which the mass was localized in the buccal region. The patient was male and had no family history.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Because those in the facial area mostly do not regress spontaneously and pose cosmetic problems for the patient, they are treated surgically by total excision. 11 In our study, VHC was identified only in 1 case, in which the mass was localized in the buccal region. The patient was male and had no family history.…”
Section: Discussionmentioning
confidence: 50%
“…Except for the visible swelling, it follows an asymptomatic course. 10,11 It has been demonstrated that it may be sporadic or may be inherited as an autosomal dominant disorder. 11 No racial or gender predisposition has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation